A method for preparing nanoscale monodisperse MXene materials
The method of primary and secondary ball milling with specific parameters and etching effectively addresses the inefficiencies of existing MXene production, enabling rapid and high-quality production of nanoscale MXene materials with controlled particle size distribution.
Patent Information
- Application Number
- CN202411069062.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-06
AI Technical Summary
Existing methods for preparing nanoscale MXene materials are time-consuming, have low yield, and struggle with controlling particle size distribution, often requiring lengthy etching and ball milling processes with inefficient post-processing.
A method involving primary and secondary ball milling with specific zirconium beads and parameters, followed by etching, to control particle size and distribution, reducing preparation time and improving efficiency.
Achieves rapid production of nanoscale monodisperse MXene materials with controlled particle size and improved quality by optimizing ball milling and etching processes.
Smart Images

Figure CN118598135B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a method for preparing a nanoscale monodisperse MXene material. Background Art
[0002] MXene is a graphene-like two-dimensional material, usually prepared by selectively etching the A layer from the Mn+1AXn phase. The structure of the ternary MAX phase can be described as a two-dimensional Mn+1AXn sublattice of interlaced A layers, where M is an early transition metal, A is a third or fourth main group element, and X is at least one of C and N. MAX is a layered material. The MAX phase has a hexagonal layered structure, consisting of alternating MX layers and A atomic layers. The MXs are mainly mixed covalent / metallic bond characteristics, and the MA bonds are metallic bond characteristics with weaker bonds. Under specific chemical environments, the A atomic layer can be selectively corroded to form a stable MX layer, with terminal functional groups such as -OH, -O, and -F adsorbed on the surface. This two-dimensional material is MXene.
[0003] The mesh size of conventional MAX phase raw materials ranges from about 200 to 500 mesh, with the most common being 400 mesh, and the lateral size being about 38μm. MXene is obtained by etching from the MAX phase, and the size of a single sheet is about 5-30μm (micrometer level). For some fields that have size requirements for materials, such as the biomedical field and the field of nano-drug development, it is necessary to further prepare nanoscale MXene materials. At present, conventional etching methods, such as acid etching, are mostly used to prepare nanoscale MXene materials. After obtaining a single layer of MXene, it is then subjected to ultrasound or cell pulverization, and then graded centrifugation to obtain nanoscale monodispersed MXene nanosheets.
[0004] Chinese patent application 202210035529.1 discloses a MXene and a preparation method thereof and a negative electrode for a lithium-ion battery, wherein the preparation method comprises the following steps: (1) mixing a MAX raw material with an etching solution to obtain an etched MXene; (2) using dimethyl sulfoxide as an auxiliary agent, wet ball milling the obtained etched MXene to obtain a ball-milled MXene; (3) mixing an alkali solution with the obtained ball-milled MXene, and ultrasonically treating the mixture in a protective atmosphere to obtain the MXene. When preparing MXene materials, this preparation method requires etching for 20-25 hours and then ball milling for 10-15 hours, which is time-consuming.
[0005] Chinese Patent Application 202310428581.8 A method for preparing MXene nanosheets, which uses a buffered grinding aid to assist ball milling for rapid exfoliation combined with an acid / alkaline solution etching strategy to prepare MXene nanosheets with high efficiency, high yield and scale. The method comprises the following steps: (1) mixing a ternary MAX phase precursor material and an acid or alkaline etching solution to obtain a mixed dispersion A; (2) mixing dispersion A, a buffered grinding aid and a ball milling ball, ball milling to obtain a ball milling dispersion B; (3) centrifugally washing the ball milling dispersion B with deionized water to obtain a mixed precipitate C; (4) dispersing the mixed precipitate C in a dispersion solvent, ultrasonically or vortexing, and centrifugally separating to obtain a MXene nanosheet dispersion. The ball milling time of the preparation method is about 12 hours.
[0006] The existing technology has the following problems: (1) The process of etching MAX to obtain MXene is time-consuming. For example, it takes 4 days to react from Cr2AlC to Cr2C, and 8 days to react from Mo4VAlC4 to Mo4VC4. In addition, the time for ball milling and etching is relatively long. (2) The process of obtaining nano-scale MXene from micron-scale MXene has a low yield and the post-processing is time-consuming and cumbersome. After etching from top to bottom to obtain micron-scale materials, they are crushed again and the graded centrifugation steps must be repeated many times to finally obtain nanosheets. (3) The ultrasonic crushing method combined with graded centrifugation cannot effectively control the particle size. The obtained MXene materials are only nano-scale or micron-scale, such as 100-500nm, 1-3μm, etc., and the particle size distribution range is large.
[0007] In view of this, the present invention proposes a method for effectively controlling the particle size distribution of MXene materials and reducing the preparation time to solve the shortcomings of the prior art. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing nanoscale monodisperse MXene materials, which can effectively control the particle size and distribution of MXene materials, reduce preparation time and improve preparation efficiency.
[0009] To achieve the above-mentioned purpose of the invention, the technical solution of the present invention is as follows:
[0010] A method for preparing a nanoscale monodisperse MXene material comprises the following steps:
[0011] (1) Primary ball milling: The MAX phase raw material and the dispersant are mixed to obtain a mixed solution, and the mixed solution is ball milled with 0.5-1.0 mm zirconium beads at 2400-3200 rpm for 2-5 h to obtain raw material 1;
[0012] (2) Secondary ball milling: the raw material 1 obtained in step (1) is ball milled with 0.15-0.45 mm zirconium beads at 2400-3200 rpm for 1-4 h to obtain raw material 2;
[0013] (3) Etching treatment: The raw material 2 obtained in step (2) is etched by wet acid etching or vapor phase etching to obtain the nanoscale monodisperse MXene material.
[0014] Preferably, in step (1), the MAX phase raw material is selected from at least one of Ti3AlC2, Ti2AlC, Cr2AlC, V2AlC, Nb2AlC, V4AlC3, Nb4AlC3, Mo2Ga2C, Ti3SnC2, and Mo4VAlC4.
[0015] Preferably, in step (1), the mesh size of the MAX phase raw material is 200-600 mesh, more preferably 200 mesh.
[0016] Preferably, in step (1), the dispersant is selected from at least one of water, ethanol, N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), and N,N-dimethylformamide (DMF), and is more preferably water or ethanol.
[0017] Preferably, in step (1), the solid content of the mixed solution is 5-80%, more preferably 40-60%, and even more preferably 50%.
[0018] Preferably, in step (1), the mass ratio of the MAX phase raw material to the zirconium beads is 1:0.8-5, more preferably 1:1-3, and most preferably 1:1.8.
[0019] Preferably, in step (1), the mixed solution is ball-milled with 0.6-0.8 mm zirconium beads at 2600-3000 rpm for 2-4 h.
[0020] Further preferably, in step (1), the mixed solution is ball-milled with 0.6-0.8 mm zirconium beads at 2800 rpm for 3 h.
[0021] Preferably, in step (1) and step (2), the material of the zirconium beads is selected from at least one of 95 zirconium oxide, 65 zirconium oxide balls, yttrium-stabilized zirconium oxide beads, cerium-stabilized zirconium oxide beads, 80 zirconium beads and zirconium silicate beads, and more preferably 95 zirconium oxide.
[0022] Preferably, in step (2), the raw material 1 obtained in step (1) is ball-milled with 0.3-0.4 mm zirconium beads at 2600-3000 rpm for 1-3 h.
[0023] Further preferably, in step (2), the raw material 1 obtained in step (1) is ball-milled with zirconium beads of 0.3-0.4 mm at 2800 rpm for 2 h.
[0024] Preferably, in step (3), the wet acid etching comprises the steps of: introducing HCl gas into the raw material 2 and keeping the temperature at 600-800° C. for 20-40 min.
[0025] Further preferably, in step (3), the wet acid etching comprises the steps of: introducing HCl gas into the raw material 2 and keeping the temperature at 700° C. for 30 min.
[0026] Preferably, in step (3), the vapor phase etching comprises the steps of: immersing the raw material 2 in a mixture of lithium fluoride and hydrochloric acid, stirring, and simultaneously subjecting the raw material 2 to ultrasonic bath treatment, taking the supernatant, and repeatedly centrifuging until the pH value of the supernatant is 5.8-6.2.
[0027] In the present invention, the term "ultrasonic bath treatment" refers to treatment with an ultrasonic cleaning machine. Since ultrasonic cleaning machines all include a sonic bath for water and cleaning items, this treatment method is called medium. For example, in the medium ultrasonic bath treatment, the ultrasonic power is 40 / 80KHz, the time is 30 minutes, and the temperature is room temperature.
[0028] Further preferably, in step (3), the vapor phase etching comprises the steps of:
[0029] The raw material 2 was immersed in a mixture of 20 mL of lithium fluoride and hydrochloric acid at room temperature for 3 hours, stirred at room temperature for 24-30 hours, and simultaneously subjected to ultrasonic bath treatment. The supernatant was taken, water was added, and centrifuged at 3500 rpm for 5 min, and the process was repeated until the pH of the supernatant was 5.8-6.2.
[0030] The beneficial effects of the present invention are:
[0031] The present invention provides a method for preparing a nano-scale monodisperse MXene material. By selecting a MAX phase raw material with a specific particle size, and through a secondary ball milling process, and selecting specific ball milling parameters, good control of the particle size is achieved, and subsequent etching treatment is greatly promoted, which significantly shortens the preparation time of the nano-scale monodisperse MXene material and improves the material quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The particle size distribution diagram of the raw material after ball milling for 0 min (A) and 60 min (B) in Example 1 of the present invention.
[0033] Figure 2 The particle size distribution diagram of the raw material after ball milling for 120 min (A) and 180 min (B) in Example 1 of the present invention.
[0034] Figure 3 The particle size distribution diagram of the raw material after ball milling for 240 min (A) and 300 min (B) in Example 1 of the present invention.
[0035] Figure 4 This is the TEM image of Cr2C obtained by etching the MAX phase in Example 1 of the present invention.
[0036] Figure 5 This is the TEM image of Cr2C obtained by etching the MAX phase in Example 2 of the present invention. DETAILED DESCRIPTION
[0037] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is only an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the invention of the present invention based on the disclosed content, and they should also fall within the scope of the present application.
[0038] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.
[0039] In the following examples, the Cr2AlC MAX phase raw material was purchased from Nanjing Muke Nanotechnology Co., Ltd. with a product number of 100456.
[0040] Example 1
[0041] 1kg 200 mesh Cr2AlC MAX phase raw material is added to 1L water to prepare a solution with a solid content of about 50%, then the prepared solution is poured into a ball mill, 1800g 0.6-0.8mm zirconium beads are added, and the material of the zirconium beads is 95 zirconium oxide. First, 2800 rpm ball milling is performed for 3h, then 1800g 0.3-0.4mm zirconium beads are replaced, and the material of the zirconium beads is 95 zirconium oxide. Then, 2800 rpm ball milling is performed for 2h to obtain a Cr2AlC MAX phase of about 500nm. Then, the obtained Cr2AlC MAX phase is placed in a high-temperature tube furnace, HCl gas is introduced, the temperature is raised to 700℃, and the temperature is kept for 30min under HCl gas to obtain Cr2C powder.
[0042] Example 2
[0043] 1kg 200 mesh Cr2AlC MAX phase raw material was added to 1L water to prepare a solution with about 50% solid content. The prepared solution was then poured into a ball mill, and 1800g 0.6-0.8mm zirconium beads were added. The material of the zirconium beads was 95 zirconium oxide. The first rough grinding was carried out at 2800 rpm for 3h, and then 1800g 0.3-0.4mm zirconium beads were replaced. The material of the zirconium beads was 95 zirconium oxide. The fine grinding was carried out at 2800 rpm for 2h to obtain a Cr2AlC MAX phase of about 500nm. The Cr2AlC MAX phase (2 g) was immersed in a mixture of 20mL lithium fluoride and hydrochloric acid at room temperature for 3 hours. The LiF and HCl mixture was prepared by dissolving 6 g LiF in 100 mL 6 M HCl. The suspension was stirred at room temperature for more than 24h and ultrasonic bath treatment was performed to promote shedding and interlayer. Take the supernatant, add deionized water, and centrifuge at 3500 rpm for 5 min to remove soluble fluoride. Repeat this process until the pH of the supernatant is close to 6, and Cr2C powder can be obtained.
[0044] Example 3
[0045] The difference from Example 1 is that the first ball milling time is 1 hour, and the second ball milling time is 1 hour. The rest are the same.
[0046] Example 4
[0047] The difference from Example 1 is that the first ball milling time is 2 hours, and the second ball milling time is 1 hour. The rest are the same.
[0048] Example 5
[0049] The difference from Example 1 is that the material of the zirconium beads used is 65 zirconium oxide balls, and the rest is the same.
[0050] Example 6
[0051] The difference from Example 1 is that the particle size of the zirconium beads in the first ball milling is 0.3-0.5 mm, and the particle size of the zirconium beads in the second ball milling is 0.1-0.2 mm. The rest are the same.
[0052] Example 7
[0053] The difference from Example 1 is that the solid content of the raw material solution is 50%, and the rest is the same.
[0054] Example 8
[0055] The difference from Example 1 is that the solid content of the raw material solution is 40%, and the rest is the same.
[0056] Example 8
[0057] The difference from Example 1 is that the solid content of the raw material solution is 60%, and the rest is the same.
[0058] Example 9
[0059] The difference from Example 1 is that the solid content of the raw material solution is 80%, and the rest is the same.
[0060] Comparative Example 1
[0061] 1kg 200 mesh Cr2AlC MAX phase raw material is added to 1L water to prepare a solution with a solid content of about 50%, then the prepared solution is poured into a ball mill, 1800g 0.6-0.8mm zirconium beads are added, and the zirconium beads are made of 95 zirconium oxide. The ball milling is performed at 2800 rpm for 5h to obtain a Cr2AlC MAX phase of about 500nm. The obtained Cr2AlC MAX phase is then placed in a high-temperature tube furnace, HCl gas is introduced, the temperature is raised to 700℃, and the temperature is kept under HCl gas for 30min to obtain Cr2C powder.
[0062] Comparative Example 2
[0063] 1kg 200 mesh Cr2AlC MAX phase raw material is added to 1L water to prepare a solution with a solid content of about 50%, then the prepared solution is poured into a ball mill, 1800g 0.3-0.4mm zirconium beads are added, and the zirconium beads are made of 95 zirconium oxide. The ball milling is performed at 2800 rpm for 5h to obtain a Cr2AlC MAX phase of about 500nm. The obtained Cr2AlC MAX phase is then placed in a high-temperature tube furnace, HCl gas is introduced, the temperature is raised to 700℃, and the temperature is kept under HCl gas for 30min to obtain Cr2C powder.
[0064] Comparative Example 3
[0065] The difference from Example 1 is that 1.0-1.2 mm zirconium beads are used in the first ball milling, and the rest are the same.
[0066] Comparative Example 4
[0067] The difference from Example 1 is that the rotation speed of the two ball millings is 3500 rpm, and the rest are the same.
[0068] Comparative Example 5
[0069] The difference from Example 1 is that in the two ball millings, the mass ratio of the MAX phase raw material to the zirconium beads is 1:0.5, and the rest are the same.
[0070] Comparative Example 6
[0071] The difference from Example 1 is that in the two ball millings, the mass ratio of the MAX phase raw material to the zirconium beads is 1:6, and the rest are the same.
[0072] Comparative Example 7
[0073] 1kg 200 mesh Cr2AlC MAX phase raw material was ground in a mortar for 3h, then the ground raw material was added to 1L water to prepare a solution with a solid content of about 50%, and then 1800g 0.3-0.4mm zirconium beads (95 zirconium oxide) were added to the prepared solution, and then ball milled at 2800 rpm for 2h to obtain a Cr2AlC MAX phase of about 500nm. The obtained Cr2AlC MAX phase was then placed in a high-temperature tube furnace, HCl gas was introduced, the temperature was raised to 700℃, and the temperature was kept under HCl gas for 30min to obtain Cr2C powder.
[0074] Results test:
[0075] 1. Particle size distribution:
[0076] Distilled water was selected as the dispersion medium of the raw materials. The sample was first mixed with distilled water to prepare a suspension. The particle size distribution of the Cr2AlC MAX phase raw material and the ball-milled MAX phase raw material was analyzed using a laser particle size analyzer.
[0077] from Figure 1 , Figure 2 , Figure 3 It can be seen that compared with the original particle size D50: 35.251 μm, the particle size of the MAX phase after different ball milling times has been significantly reduced, especially after 300 minutes of ball milling, the particle size has significantly dropped to the nanometer level (D50: 0.499 μm).
[0078] The particle size test results are as follows:
[0079]
[0080] The results show that examples 1-2, 8-9 all obtained nano-scale MXene materials, and the particle size of example 3 was too large. Comparative Examples 1 and 2 show that the nano-scale of the material is significantly promoted by the secondary ball milling process, and it is difficult to achieve this technical effect by using a single ball mill. Comparative Example 3 shows that the size of the zirconium beads will have a significant effect on the results. Comparative Examples 4, 5, and 6 show that the ball milling speed and the mass ratio of the MAX phase raw material and the zirconium beads will affect the product particle size, among which the mass ratio of the MAX phase raw material and the zirconium beads has a greater effect on the particle size. Comparative Example 7 uses a process of first grinding and then ball milling, and the product particle size is too large, making it difficult to obtain a nano-scale product.
[0081] In summary, by selecting MAX phase raw materials with specific particle size, and through the secondary ball milling process, selecting specific ball milling parameters, good control of the particle size can be achieved, and the subsequent etching treatment is greatly promoted, which significantly shortens the preparation time of nanoscale monodisperse MXene materials and improves the material quality.
[0082] 2. Morphology characterization:
[0083] like Figure 4 As shown in the figure, the TEM image of the powder Cr2C prepared in Example 1 shows obvious two-dimensional layered features, which also proves that it belongs to the MXene structure. This shows that the Cr2AlC MAX phase can also produce a good etching effect under HCl gas. Figure 5 As shown in the electron microscope image, the microscopic morphology of the Cr2C powder obtained by wet acid etching is similar. The microscopic TEM image can prove the high efficiency of the vapor phase etching method. At the same time, the advantage of this method is that no intercalation agent needs to be added after etching, and an almost single-layer Cr2C MXene is obtained in one step, which is relatively more fluffy.
[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nanoscale monodisperse MXene material, characterized in that: The following steps are involved: (1) primary ball milling: a MAX phase raw material and a dispersant are mixed to obtain a mixed solution, and the mixed solution is ball milled with zirconium beads of 0.5-1.0 mm at 2400-3200 rpm for 2-5 h to obtain raw material 1; the MAX phase raw material is selected from at least one of Ti3AlC2, Ti2AlC, Cr2AlC, V2AlC, Nb2AlC, V4AlC3, Nb4AlC3, Mo2Ga2C, Ti3SnC2, and Mo4VAlC4, and the mass ratio of the MAX phase raw material to the zirconium beads is 1:0.8-5; (2) Secondary ball milling: the raw material 1 obtained in step (1) is ball milled with 0.15-0.45 mm zirconium beads at 2400-3200 rpm for 1-4 h to obtain raw material 2; (3) Etching treatment: The raw material 2 obtained in step (2) is etched by wet acid etching or vapor phase etching to obtain the nanoscale monodisperse MXene material.
2. The preparation method according to claim 1, characterized in that: In step (1), the mesh size of the MAX phase raw material is 200-600 mesh.
3. The preparation method according to claim 1, characterized in that: In step (1), the mesh size of the MAX phase raw material is 200 mesh.
4. The preparation method according to claim 1, characterized in that: In step (1), the solid content of the mixed solution is 5-80%.
5. The preparation method according to claim 1, characterized in that: In step (1), the solid content of the mixed solution is 50%.
6. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the MAX phase raw material to the zirconium beads is 1:1.
8.
7. The preparation method according to claim 1, characterized in that: In step (1), the mixed solution is ball-milled at 2600-3000 rpm for 2-4 h using zirconium beads of 0.6-0.8 mm. In step (2), the raw material 1 obtained in step (1) is ball-milled at 2600-3000 rpm for 1-3 h using zirconium beads of 0.3-0.4 mm.
8. The preparation method according to claim 1, characterized in that: In step (1), the mixed solution is ball-milled at 2800 rpm for 3 h using zirconium beads of 0.6-0.8 mm. In step (2), the raw material 1 obtained in step (1) is ball-milled at 2800 rpm for 2 h using zirconium beads of 0.3-0.4 mm.
9. The preparation method according to claim 1, characterized in that: In step (1) and step (2), the material of the zirconium beads is selected from at least one of 95 zirconium oxide, 65 zirconium oxide balls, yttrium-stabilized zirconium oxide beads, cerium-stabilized zirconium oxide beads, 80 zirconium beads and zirconium silicate beads.
Citation Information
Patent Citations
Single-layer MXene nanosheets and preparation method thereof
CN111591992A
MXene, preparation method thereof and lithium ion battery negative electrode
CN114394595A
Preparation method of MXene nanosheet
CN116605880A
